The Influence of Financial Literacy and Access to Capital on the Financial Performance of MSMEs in Pematang Siantar City - Purba, Djuli Sjafei; Martina, Sri; Ferdila, Ferdila (Program Studi Akuntansi Universitas Simalungun, 2025)
This study aims to analyze the influence of financial literacy and access to capital on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Pematang Siantar City, both partially and simultaneously. Financial literacy is assessed based on the understanding of basic financial concepts, the ability to prepare and manage budgets, knowledge of financial products, and the ability to interpret financial statements. Access to capital is measured through the ease of loan procedures, availability of financing information, relationships with financial institutions, and the ability to meet loan requirements. Financial performance is evaluated by indicators such as revenue growth, net profit, debt repayment ability, and operational cash flow stability. This research uses a quantitative approach with a survey method, employing closed-ended questionnaires. Data were analyzed using multiple linear regression and SmartPLS. The results indicate that both financial literacy and access to capital have a significant partial effect on financial performance, and a strong simultaneous influence when combined. These findings underscore the importance of enhancing financial literacy and improving financing access to support the sustainability of micro and small enterprises